Ergonomic evaluation of workers at a cabinet mill and assembly plant: health hazard evaluation report - USA. National Institute for Occupational Safety and Health; Ramsey, Jessica; Dang, Bich; Habes, Daniel (Cincinnati, 2008)
"The Health Hazard Evaluation (HHE) program responded to a management request at a cabinet mill and assembly plant. The request concerned potential musculoskeletal hazards resulting from job tasks. The investigators found that workers use high force, awkward postures, and repetitive motions, all of which increase their risk for developing musculoskeletal disorders. Most of the reported injuries were musculoskeletal disorders involving the upper extremities. It was recommended that managers provide adjustable tables and carts to reduce the physical stresses that employees endure during work practices. Investigators also recommended that the facility consider improving tool design to reduce vibration and to decrease the force required to handle and operate tools effectively. This is the final report."